Age-related changes in biochemical bone profile in thalassemic children - Ehab S. Abd El-Moneim; Mohammed A. Zolaly; Zakaria M. Al-Hawsawi; Abeer A. Abdelmoneim; Mostafa M. Abosdera (Pediatrics and Neonatology)
Background: Osteopathy is an important cause of morbidity in β-thalassemia major (TM). Although many of the etiopathological factors implicated in thalassemic osteoporosis commence in early disease phases during childhood, limited information exists on bone turnover in children with TM. This study was conducted with the objective to compare bone turnover markers (BTMs) in thalassemic children at different ages. Methods: In a cross sectional case control study, 47 children (age range, 1.5–18 years) with TM were recruited. BTMs were compared to eighteen age- and sex-matched healthy controls and to 16 adults (age range, 19.67–31.08 years) with TM. Results: Thalassemic children displayed unbalanced bone turnover with an increased bone resorption (shown by high levels of tartrate-resistant acid phosphatase 5b (TRACP5), receptor activator of nuclear factor-kappa B ligand (sRANKL) and sRANKL/osteoprotegerin (OPG) ratio) and a decreased bone neoformation (shown by low levels of osteocalcin (OC)) when compared to healthy children. TRACP5b was the only BTMs studied that showed a significant correlation with age in thalassemic children. For the whole thalassemic children group, regression analyses showed an influence of sex hormones replacement therapy on TRACP5b; pretransfusion hemoglobin and splenectomy on sRANKL; pretransfusion hemoglobin on sRANKL/OPG; and pretransfusion hemoglobin and serum ferritin on OC. Conclusion: The present study confirms that TM has profound effects on bone metabolism starting from early childhood. The early onset of bone turnover disturbances in TM indicates the need to investigate possible option to intervene early. Key Words: osteopathy, bone turnover, children, thalassemia